Single-Center Overview of Pediatric Monogenic Autoinflammatory Diseases in the Past Decade: A Summary and Beyond - Wang, Wei; Yu, Zhongxun; Gou, Lijuan; Zhong, Linqing; Li, Ji; Ma, Mingsheng; Wang, Changyan; Zhou, Yu; Ru, Ying; Sun, Zhixing; Wei, Qijiao; Dong, Yanqing; et al. (Frontiers in Immunology, 2020)
Objective: Autoinflammatory diseases (AIDs) are disorders of innate immunity caused either by monogenic factors or polygenic origins. Our aim was to provide the phenotypes and genotypes of Chinese pediatric monogenic AID patients. Methods: A total of 288 pediatric patients with clinical phenotypes suspicious for AIDs were studied at the Department of Pediatrics of Peking Union Medical College Hospital between November 2008 and May 2019. All patients were genotyped by Sanger sequencing, and/or primary immunodeficiency gene panel and/or whole exome sequencing. A final definite diagnosis was made when the clinical features and genetic variants mutually verified. Results: Of the 288 patients, 79 (27.4%) were diagnostic of monogenic AIDs, including 33 patients with inflammasomopathies, 38 patients with non-inflammasome related conditions, and 8 patients with type 1 interferonopathies. Skin disorders (76%), musculoskeletal problems (66%) and fever (62%) were the most common clinical features. Other features included central nervous system abnormalities (15%), eye disorders (16%), ear problems (9%), cardiopulmonary disorders (8%), and symptoms involving gastrointestinal tract system (25%). Many of the genetic variants were not reported elsewhere. Conclusions: The present study demonstrated 18 kinds of monogenic AID patients in pediatric Chinese population, with fever, skin problems and musculoskeletal system disorders being the most prevalent clinical features. This report was an overview of monogenic AIDs diagnosed in a pediatric tertiary center and also a reflection of the phenotypic and genotypic features among Chinese pediatric monogenic AID patients.